Reactivation of UV-Irradiated Herpes Simplex Virus Type 2 in Cockayne's Syndrome and Xeroderma Pigmentosum Cells - Ryan, David (My University, 1983)
Host cell reactivation (HCR) of UV-irradiated (UV'd) herpes simplex virus type 2 (HSV-2), capacity of UV'd cells to support HSV-2 plaque formation and UV enhanced reactivation (UVER) of UV'd HSV-2 were examined in human fibroblasts. The cells were derived from four Cockayne's Syndrome (CS) patients, 5 xeroderma pigmentosum (XP) patients and 5 normal patients. Survival curves for HCR of HSV-2 plaque formation showed 2- components. HCR was not significantly different in the CS strains and an XP variant strain compared to normal, whereas all excision deficient strains showed a significant reduction in HCR. The o37 values for the delayed capacity curves were in the range 8.6-12.4 J/m2 for the normal strains, 3.1-5.1 J/m2 for the CS strains, 6.7 J/m2 for an XP variant strain and between 0.40-1.98 J/m2 for the XP excision deficient strains examined. UVER was also examined for HSV-2 UV-irradiated to survival levels of 10-2 and 10-3 in unirradiated cells. Maximum delayed UVER was observed in normal strains at a UV dose of 15 J/m2 to the virus. Maximum UVER in CS cells was detected at a UV dose of 5 J/m2 to the cells, in XP excision deficient cells maximum UVER occurred at doses ranging from 0.5-2.5 J/m2 to the cells, and in XP variant maximum UVER occurred at 10 J/m2 to the cells. In all cell strains the level of UVER increased with increasing UV dose to the virus. Results are discussed in terms of the repair defects of CS and XP cells and their relationship to possible viral repair functions. In addition, the possible existence of an inducible DNA repair response is discussed in terms of the results of this study.
Reactivation of UV-Irradiated Herpes Simplex Virus Type 2 in Human Cells
Keywords: herpes simplex virus; xeroderma pigmentosum; cockayne's syndrome; uv-irradiation